Distopik Filmler Üzerinden Mekansal Okumalar - Günal, Hazal (Fen Bilimleri Enstitüsü, 2015)
Tez çalışması, distopya kavramının, mimarlık ile kurduğu ilişkiden yola çıkmıştır. Distopyanın, bulunduğu döneme dair sorunları, karamsar bir gelecek senaryosu üzerinden dillendirmesi, distopyaya eleştirel bir tutum kazandırır. Distopyanın, güncel sorunları aktarmaktaki öngörüsü, en çok sinemada ve edebiyatta karşılık buluşmuştur. Sinemanın, bu tez çalışmasında kıymetli olmasının nedeni ise, distopik kurguların temelindeki kaygıların, sinemada mekan üzerinden aktarılmasıdır. Çalışmada öncelikli olarak distopyanın yararlandığı anlatılar incelenmiştir. Bu anlatılara bakılırken, distopyanın bilimkurgu ile kurduğu ilişkiden yararlanılmıştır. Distopyanın doğuşunda önemli bir rol oynayan bilimkurgu, distopyanın daha iyi anlaşılabilmesi ve distopya bilimkurgu arasındaki farkın vurgulanabilmesi için tezde bilimkurgu tarihini bu bağlamda incelenmiştir. Distopyanın edebiyat ve sinemada içerisindeki var oluşu, bilimkurgu tarihinin sürekliliği içerisinde değerlendirilmiştir. Bu bağlamda ilk olarak bilimkurgu edebiyatının ve distopya edebiyatının tarihsel gelişim süreçlerine bakılmıştır. Edebiyat ile kurulan ilişki, distopyanın sinema ile buluşmasındaki ilk basamaktır. Bir sonraki aşamada, distopyanın sinemada var oluşu ele alınmıştır. Sinema, distopyanın mimarlık ile kurduğu ilişki açısından önemli bir anlatıdır; çünkü distopik filmlerin öngörüleri en çok mekanda karşılık bulur. Mekan, distopyanın ele aldığı sorunlara ışık kullanmakta kullandığı bir araçtır. Tez çalışmasında, distopyanın mekan ile olan birlikteliği göz önünde bulundurularak, distopik filmler üzerinden bir mekan okuması yapılır. Mekan okumasının yapıldığı distopik filmler seçilirken, bilimkurgu sineması tarihi içersindeki kırılmalara bakılmıştır. Seçilen filmlerin deşifresi, distopyanın temel bileşenleri olarak ele alınan, zaman ve mekan kavramları üzerinden yapılmıştır. Filmlerin deşifresinin sonucunda, bu bileşenleri oluşturan mekansal elemanlar belirlenmiştir. Bu sayede distopik mekan kurgusu tariflenmiştir. Tezin ikinci bölümünde, tariflenen bu kurgu ve distopik mekanı oluşturan bileşenlerden yola çıkılarak, kentsel bir okuma yapılmıştır. Bu kentsel okuma için belirlenen saha çalışması Taksim - Maslak aksı üzerinde gerçekleştirilir. Çalışmada aks üzerinde yer alan yapıların, kent ve özne ile olan ilişkileri incelenmiştir. Yapılan incelemelerle kentte var olan distopik mekanlar, bileşenleri doğrultusunda deşifre edilip, sınıflandırılmıştır. Bu çalışma sonucunda, İstanbul kentindeki kimi distopik mekanlar açığa çıkarılmış ve kentin distopik kurgusuna dair bir kesit sunulmuştur.

The relationship between dystopia and architecture is the main motivation of the thesis. Crtitizing the daily situations through a future fiction makes dystopia didactic and critizing. This critical way of thinking in dystopia mostly express its foresight in literature and cinema. Especially throught cinema dystopia makes such critics by using space. Dystopia literaly means bad place. It warns humans by creating a future fiction. Those fictions show the worst and the most desperate conditions of human life. Each dystopia is didactic for society through a future threatment. Instead of showing the future dystopia defines more its own term. It is a brutal critic of a daily life. It aims to show the default of the system and people to be aware. As a reason of that reading cities through dystopia could help us to criticize space and could bring an alternative way of thinking in architectural field. Nowadays daily life of cities are under control of capitalism. Capitalism as a system gets its power from consumption. Consumption could stay alive by production. More production means more consumption which makes capitalism stronger. As a reason of that we could say speed is the most important tool of the capitalist system. Therefore technology which increases the speed, is the best supporter of capitalism. Since technology got in our daily lifes, cityscapes and architectural presentations started to change. New architectural presentations bring us a new perception of space and a new dimensions. Cityscapes change faster by technology. Those demolitions are not letting subject to have a relationship between cities. This situation starts to make subject to lose its role in cities. The thesis aims to read dytopian spaces in İstanbul and analyse the effects of the system in urban space and urban life. As a reason of that first of all, the dystopian presentations were examined in this work. The relationship between dystopia and science fiction was disgussed while looking at those dystopian work. To understand better the difference between science fiction and dystopia, and also to understand how dystopia exists, science fiction was also examined in this study. The existence of dystopia was disgussed through the history of science fiction literature and cinema. In this case first this study looks at the development of dystopian literature throught history of science fiction literature. Because literature is the first steps which connects dystopia to cinema. On the other hand literature is the first presentation of the dystopia that is why to understand better the dystopian concept, literature used as a first step. In the next part the existence of dystopia in cinema was examined. Because of creating a strong connection between dystopia and architecture, cinema has a very important place. The critics of dystopia is mostly projected by space because space is the most important tool of dystopia while telling the problems of daily life. Because of having this relationship between space and dystopia in cinema, this study reads spaces throught dystopian movies. The main item which effect choosing the dystopian movies in thesis is the breaking points in history of science fiction movies. As a result of this attitude the dystopian movies were selected. After this selection space in those dytopian movies which are Metropolis (1927), Things to Come (1936), Fahrenheit 451 (1966), Clockwork Orange (1971), Blade Runner (1982), 1984 (1984), Brazil (1985) and La Antena (2007) were analysed. According to that the main components of dystopian movies are time and space. That’s why those movies were examined through time and space. This study gives the elements which creates the dystopian space. The first component of dystopian movies “space” defined as grotesque space in this study. To understand better the concept of grotesque, first the development of grotesque is examined. This examination shows how grotesque was transformed from being a figurative presentation to space. In this case, Robert Wilson’s art works which are the first examples of grotesque space, are analysed to define the space better. Later on those tools which Robert Wilson uses, are searched in dystopian movies. At the end of analysing eight choosen dystopian movies, different elements are found to create grotesque space. Those physical elements are used to build up the cinematographic atmosphere in the movies. However those tools also produce a new perception of space. By the datas while analysing dystopian movies this relationship between subject and space is also examined. All those datas classified in a scheme as a dystopian city guide. The second component of dystopian movies “time” defined as retro future in this study. Time in dystopian fiction has a multi layered structure. The dialectic juxtaposition of future and primitive forms in space, breaks the chronology of time. Time doesn’t run in a linear order of past present and future. The course of the movie combines each seperated element of time and creates a new form. This is offers a phenomological blury to time which defined as retro future. Retro future occurs the main fiction of dystopia and helps to build a grotesque space. The elements of space which makes time vague is examined and classified at the end of this part. The classification also consist of the perception of subject. Those datas which creates retro future are summed up in a scheme to use as a dystopian city guide. In the second part of the thesis, Istanbul as a city was read by the definition of dystopian space and by the element of it. For this case study the area which is selected is the axis between Taksim and Maslak. This axis is also a kind of chronological development of Istanbul. The deconstruction of the city starts from Taksim and the historical process continues on this present axis. That’s why this axis has multi layers. Those layers overlaped and creates phenomenological spaces. This case study also decompose them to analyse and recombine them as a dystopian fiction. The elements which creates the dystopian space used as a filter while doing this study. The physical elements of space are used to find the dystopian spaces in this axis. The effects of dystopian spaces on subject examined through those datas in the city. The varibles of city depend on the dystopian space and the constant datas overlaped. This superposition shows the “how dystopian spaces could exists in daily life?” This case study creates a dystopian mapping of the choosen axis. Analysing the city through dystopia creates a dystopian fiction of Istanbul. On the other hand it shows dystopia is not a future projection or just a fiction. Dystopia is inside the space and each city contains its own dystopia. In this sense it claims that searching for dystopian spaces in cities and analysing them would raise awareness of the people. Capitalist cities makes buildings to loose their identy. This occurs a gap between the subject and perception of space in urban space. This study aims to shows those gaps by analysing the dynamics of dystopian space. To solve the problem of nowadays daily life in cities, the fisrt step is defining them. Lack of relationship betwen space and subject makes collective memory faded. However by showing the default of this connection could prevent collective memory from being lost. In this sense dystopia by its nature offers to show the problems of daily life of its term and warn people for future threats. If we read the didactics of dystopia through space and urban space, it could shows us the dynamics and critics of daily life. However dystopia is not prevision, it is an actual analyse. This analyse in the study is taken as a section of a city. It could diversify, recreate or overlap. The different and new relations of the dystopian city readings could offer new way of thinking in design process while raising the awareness of the subject. Considering all those reasons dystopia as a concept is a very helpful for architecture. This study claims that dystopian way of reading spaces could create a new desinging process, a new perceptions of space and a reproduction of space. This is possible by analysing the daily life of cities and finding the gaps in urbans spaces because each space include its own dystopia.
Spatial Readings Through Dystopian Movies
Tez (Yüksek Lisans) -- İstanbul Teknik Üniversitesi, Fen Bilimleri Enstitüsü, 2015
Thesis (M.Sc.) -- İstanbul Technical University, Institute of Science and Technology, 2015
Keywords: Distopya; Sinema; Mekan; Mimarlık; Dystopia; Movie; Space; Mimarlık